2019
DOI: 10.1115/1.4042470
|View full text |Cite
|
Sign up to set email alerts
|

Flow Behavior in Radial Vane Disk Brake Rotors at Low Rotational Speeds

Abstract: The flow behavior through the vented channel of a brake disk determines its thermal performance, viz. its resistance to brake fade, brake wear, thermal distortion, and thermal cracking. We present experimental results of the flow characteristics inside the vented channel of a radial vane brake rotor with a selected number of vanes (i.e., 18, 36, and 72) but constant porosity (ε ∼ 0.8) at low rotational speeds (i.e., 25 rpm ≤ N ≤ 400 rpm). Using bulk flow and velocity field mapping measurement techniques, we ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 30 publications
2
8
0
Order By: Relevance
“…A linear dependence was observed between the volumetric flow rate ( Q ) and rotational speed ( n ) of the vented brake disc, which was consistent with the findings of many other studies. 2,3,8,14,32,33…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A linear dependence was observed between the volumetric flow rate ( Q ) and rotational speed ( n ) of the vented brake disc, which was consistent with the findings of many other studies. 2,3,8,14,32,33…”
Section: Resultsmentioning
confidence: 99%
“…They also adopted the Dittus–Boelter equation to estimate the passage Nu e and applied power b = 0.93, which is double the value of the one applied in equation (15) and demonstrated that Ω v,r corresponds to Re e 2 , which is apparent because the flow rate and radial velocity component increased linearly with rotational speed. Finally, they compared their results with those of prior studies conducted by Sisson, 39 Tirovic et al, 40 and McPhee and Johnson.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Belhocine and Ghazaly (2016) developed FE model of the whole disc brake assembly and validated by using experimental modal analysis. Atkins et al (2019) presented a particle image velocimetry flow measurement of air flow in the ventilation channels, thus cooling the disc down during braking operations.…”
Section: Introductionmentioning
confidence: 99%